Tobacco control attitudes and perception of smoke-free area (KTR) implementation on health and non-health students in Universitas Mulawarman - Lies Permana; Annisa Nurrachmawati; Nur Rohmah; Rina Tri Agustini; Masithah Masithah; Khumairotul Zahro (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2026)
Introduction: In accordance with Samarinda Mayor Regulation No. 51 of 2012, the Faculty of Public Health at Universitas Mulawarman (Unmul) has enforced a Smoke-Free Area (KTR) policy since 2016. However, this implementation remains largely restricted to health-related faculties, leaving other areas of the university without consistent tobacco control measures. The lack of continuous health promotion initiatives has contributed to persistent smoking habits among students across the wider campus. This study aims to compare the perceptions of students from health and non-health faculties regarding tobacco control and evaluate their views on the current implementation of the KTR policy.Methods: This research employed a quantitative, cross-sectional survey design. Data was collected online between March and April 2024 using the Global Health Professional Student Survey (GHPSS). Utilizing purposive sampling, the study gathered 215 respondents, consisting of 123 health students and 92 non-health students. Data were analyzed using the Mann-Whitney test.Results: The results reveal a statistically significant difference in perceptions regarding tobacco regulation (P-value = 0.0001). Students in non-health fields tended to have a negative attitude toward tobacco control (65.7%), whereas health students demonstrated a positive perspective (67.6%). Furthermore, there was a significant difference in perceived KTR implementation (P-value = 0.000); only 22% of health students reported observing smoking on campus, compared to 83.7% of non-health students. Notably, among non-health students, those with positive attitudes toward tobacco control showed strong support for the KTR policy (87.3%), with 15.2% favoring strict sanctions for policy violations.Conclusion: The findings underscore the urgent need to expand the KTR policy to all faculties at Universitas Mulawarman. It is critical to develop targeted advocacy and educational programs that address the specific needs of the entire academic community to ensure effective and comprehensive smoke-free campus implementation.